Perbandingan Kadar Metabolit Sekunder Ekstrak Akar Wangi (Vetiveria zizanioides L.) Berdasarkan Faktor Naungan Guna Membantu Perkuliahan Kimia Bahan Alam - agustin, rizki dwi; Hakim, Aliefman; Ariani, Sunniarti (FKIP University of Mataram, 2024)
This research aims to determine the comparison of secondary metabolite levels in vetiver root plants and to develop a bulletin media expected to support the teaching of Natural Product Chemistry. The research method used is an experiment and the 4D (define, design, develop, disseminate) Research and Development model by Thiagarajan. The research was conducted in a chemistry laboratory, analytical laboratory. The distribution of questionnaire sheets was in the classroom. Vetiver root extracts used in this study were sourced from plants based on shading factors. The experiment was carried out in two stages, namely phytochemical screening and GC-MS analysis. Based on the conducted tests, it was found that the percentage of secondary metabolite content in vetiver root extracts from unshaded samples was higher compared to shaded samples. In the media development, purposive sampling technique was used and the sample consisted of students from the 2020 Chemistry Education program in the seventh-semester, who had programmed and attended Natural Product Chemistry lectures. Data collection for the development of the bulletin media was carried out using validity sheets and student response questionnaires. The validity test conducted by experts obtained a validity value of 0.9, which falls into the highly valid category. In the limited trial, a practicality percentage of 86% was obtained, which falls into the highly practical category. Therefore, it can be concluded that the bulletin learning media is suitable and practical for use in the learning process.